Utilization of the Kahoot Application in PAI Learning to Increase Understanding of Grade V Students at SDN 106840 Kp. Benar Kab. Serdang Bedagai - Ranisa Ramadhani; Diajeng Tiara Anjani; Aufa Ahyana Nursya; Nursakinah Nasution; Ika Darmayanti; Kassi Syahdu Armaya (Jurnal Pendidikan Islam, 2025)
This study aims to address the issue of low student engagement and comprehension in Islamic Education (PAI) learning at SDN 106840 Kp. Benar, caused by monotonous conventional teaching methods. Using a qualitative approach and descriptive observation method, the research explores the use of the Kahoot application as an interactive game-based learning medium. Data were collected through observation, interviews, and documentation, and analyzed using the interactive analysis model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The results show that Kahoot enhances students’ motivation, engagement, and understanding of the topic Faith in the Day of Judgment. The novelty of this research lies in the implementation of Kahoot in the context of Islamic religious education at the elementary school level. It is recommended that teachers and schools integrate digital media such as Kahoot to support active learning in alignment with the Merdeka Curriculum.